Methods for extracting and sequencing DNA from low-quality samples to aid biodiversity research - Minh, Le Duc; Ha, Duong Thuy; Thanh, Nguyen Van; Ha, Nguyen Manh; Long, Dinh Doan; Tuoc, Do; Hai, Nguyen Dinh (Academia Journal of Biology, 2013)
Surveying endangered and elusive species in their natural habitat poses an immense challenge to studies using conventional methods. This reality requires new survey techniques with higher efficiency to support fieldwork. Recently, along with progresses in biotechnology, survey techniques using molecular approaches have become more accessible, promising new applications, and in many cases assisting traditional survey methods in biodiversity research. However, a major difficulty of these techniques is recovering DNA from low-quality samples collected in survey areas. To help overcome this problem, in this study, we present a simple and highly efficient method for extracting and amplifying DNA from low-quality samples applicable in Vietnam’s context. Using this method, we successfully sequenced 30 bone, cartilage, and dry skin samples from two different vertebrate animals, muntjacs Muntiacus sp., and Shanghai softshell turtle, Rafetus swinhoei. Sequences, obtained in this study, play an important role in developing phylogenetic hypotheses and assessing genetic diversity of the two groups. This method can be applied in a variety of studies in future biotic survey and biodiversity research that would be benefited from obtaining DNA sequences of low-quality samples collected in the field in Vietnam.